(untitled) (Modern information system and technologies, 2018)
The article outlines the need to control information flows and implement traffic accounting between the corporate network and Internet traffic, the principles of organizing IP traffic accounting, principles and methods for collecting traffic information. The IP packet is not copied but forwarded to the software for analysis, feedback is made to the access device using intelligent access restriction algorithms for individual clients, protocols, and others.